2020
DOI: 10.1021/jacs.9b11234
|View full text |Cite
|
Sign up to set email alerts
|

Different Reaction Specificities of F420H2-Dependent Reductases Facilitate Pyrrolobenzodiazepines and Lincomycin To Fit Their Biological Targets

Abstract: Antitumor pyrrolobenzodiazepines (PBDs), lincosamide antibiotics, quorumsensing molecule hormaomycin, and antimicrobial griselimycin are structurally and functionally diverse groups of actinobacterial metabolites. The common feature of these compounds is the incorporation of L-tyrosine-or L-leucine-derived 4-alkyl-L-proline derivatives (APDs) in their structures. Here, we report that the last reaction in the biosynthetic pathway of APDs, catalyzed by F 420 H 2 -dependent Apd6 reductases, contributes to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“… 38 Hitherto, biochemical details of these other members are scarce. Recently, Steiningerova et al 32 demonstrated that the actinobacterial enzymes LmbY, 39 HrmD, 40 among others, are F 420 H 2 ‐dependent reductases displaying the TIM barrel fold. These enzymes are involved in the last step of 4‐alkyl‐ l ‐proline derivatives (APDs) biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“… 38 Hitherto, biochemical details of these other members are scarce. Recently, Steiningerova et al 32 demonstrated that the actinobacterial enzymes LmbY, 39 HrmD, 40 among others, are F 420 H 2 ‐dependent reductases displaying the TIM barrel fold. These enzymes are involved in the last step of 4‐alkyl‐ l ‐proline derivatives (APDs) biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, 4-EtPro and 4-PrPro were characterized to be derived from L-tyrosine in the biosynthesis of lincomycins (Supplementary Figs. 11 and 12a), 22 however, no homologous genes were found in the MP pathway. As reported in GM biosynthesis, (2S,4R)-4-MePro was the product of a series of enzymatic modifications of leucine (Fig.…”
Section: In Vitro Reconstitution Of the 4-alkylproline Subpathwaymentioning
confidence: 96%
“…In 2020, Kamenik and coworkers reported the functional analysis of six Apd6 reductases: LmbY (lincosamycin), Por15 (porothramycin), SibT (sibiromycin), HrmD (hormaomycin), Lim12 (limazepine), and GriH (griselimycin). [36] In vitro analyses revealed that these enzymes strictly recognize F 420 H 2 as a cofactor to produce 44-49 (Figure 7B and C). Moreover, Por15, SibT, Lim12, HrmD reduced only the endocyclic imine bond of substrates, while LmbY and GriH also catalyzed the reduction of the exocyclic double bond in addition to the endocyclic imine bond.…”
Section: F 420 H 2 -Dependent Reductase Apd6 In Alkylproline Biosynth...mentioning
confidence: 98%